Assessment of ADMA, IMA, and Vitamin A and E Levels in Patients with Acne Vulgaris. (21st July 2020) - Tunçez Akyürek, Fatma; Saylam Kurtipek, Gulcan; Kurku, Huseyin; Akyurek, Fikret; Unlu, Ali; Abusoglu, Sedat; Ataseven, Arzu
Abstract: Background: Acne vulgaris is a common skin disease in adolescents known to be associated with oxidative stress. However, the number of studies in which oxidative stress and antioxidants are evaluated together is limited. Aims: In this study, we aimed to investigate L‐arginine/nitric oxide (NO) pathway metabolites, ischemia‐modified albumin (IMA), and vitamin A and E levels in patients with acne and its association with disease severity. Patients/Methods: Ninety patients with acne and 30 healthy adults were included in the study. The serum levels ofL‐arjinin, L‐arginine metabolites, IMA, and vitamins A and E measured in the patient and control groups. Results: Asymmetric dimethylarginine (ADMA), LN G ‐monomethyl‐L‐arginine (L‐NMMA) and symmetric dimethylarginine (SDMA), and IMA levels were significantly higher in the patients with acne than in the control group ( P  ˂ .05). The L‐arginine/ADMA ratio and citrulline and vitamin A levels were significantly lower in patients with acne than those of the controls ( P  ˂ .05). ADMA and IMA plasma levels were increased in parallel with the disease severity ( P  ˂ .05). L‐arginine/ADMA ratio, L‐arginine, citrulline, and vitamin A plasma levels decreased as the disease became severe ( P  ˂ .05). Although L‐arginine and vitamin E levels were lower in the patient group compared to the control group, the difference was not statistically significant ( P  ˃ .05). Conclusion: These results suggest that IMA and L‐arginine‐NO pathway associated with ischemia and oxidative stress may play an important role in the pathogenesis and progression of acne vulgaris.